Paclitaxel chemotherapy and vascular toxicity as assessed by flow-mediated and nitrate-mediated vasodilatation - Vassilakopoulou, M.; Mountzios, G.; Papamechael, C.; Protogerou, A.D.; Aznaouridis, K.; Katsichti, P.; Venetsanou, K.; Dimopoulos, M.-A.; Ikonomidis, I.; Papadimitriou, C.A. (Vascular Pharmacology, 2010)
Background: Antitumor activity of paclitaxel is based on promotion of abnormal microtubule (MT) assembly but it is also considered to have significant pro-inflammatory and anti-angiogenic effects in vivo and thus may cause vascular dysfunction. Methods: We studied 27 women treated with paclitaxel-containing combinations for breast or ovarian cancer. The control group was represented by 10 women with carcinoma of the uterine cervix who received low doses of weekly cisplatin as radiation sensitizer. We measured endothelial-dependent flow-mediated dilatation (FMD) and nitrate-mediated dilatation (NMD) of the right brachial artery by ultrasonography, as well as levels of the inflammatory cytokines TNF-α and IL-6 before and after chemotherapy. Results: Patients who received paclitaxel and an anthracycline had the most marked reduction in both FMD (p=0.005) and NMD (p=0.027). A significant reduction in FMD was also observed in patients treated with weekly paclitaxel (p=0.045), whereas NMD was not affected (p=0.421). Although TNF-α and IL-6 levels were different among chemotherapy groups after treatment, no significant differences were observed between levels of both markers before and after chemotherapy. Conclusion: Treatment with paclitaxel-containing combinations impairs endothelial function in vivo but endothelial function deterioration is not related to the serum levels of inflammation markers. © 2010 Elsevier Inc.
Keywords: Endothelium; IL-6; Paclitaxel chemotherapy; TNF-α; Vascular toxicity